3D Panorama Scene Reconstruction Using Kinect Camera - Mohd Razali, Daud; Nur Afzan, Murtadza; Saifudin, Razali (Asian Research Publishing Network (ARPN), 2015)
In this paper 3D panorama scene is constructed by moving around the Kinect Xbox 360 camera horizontally in indoor environment. The Kinect sensor is used because its price is cheaper than other devices but able to provide bountiful data for image processing purpose. By integrating the Kinect for windows with MATLAB, all computations, programming and processing of this project are done using the MATLAB itself. The overall system undergoes three major sectors which are the Image Acquisition Module, Image Processing and Analysis Module, and Result Processing and Displaying Module. The proposed system uses the latest "Point Cloud Processing" that was introduced in the MATLAB R2015a. Based on the result obtained, the system is able to reconstruct the 3D scene environment via offline and also real-time using the Graphical User Interface (GUI) for ease of use. The online system however, may need further improvement in terms of stabilization. Furthermore, the system is able to function with minimum lighting i.e. dark room or at night.